2020
DOI: 10.9791/10.9791/ajpanz.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

Entering the Void: Exploring the Relationship Between the Experience of Colonisation and the Experience of Self for Indigenous Peoples of Aotearoa, and the Implications for Psychotherapeutic Clinical P

Abstract: This paper explores the relationship between the experience of colonisation and the experience of self for Indigenous peoples of Aotearoa. As we celebrate the formation of Waka Oranga in 2007, and its work in the years since, the publication of this paper is particularly fitting, drawing as it does on research originally undertaken at the time of the roopu’s formation. It is based on the lead author’s 2008 Master of Psychotherapy dissertation research in which he undertook a modified systematic literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The therapy room is a site of intersecting cultural politics -especially the culture of therapy itself. This is founded on the enclosed clinical dyad, which in turn supports the Western ideal of the individual as independent, singular, and separate (Woodard, 2008). Māori clients may however be seeking a much wider collective identity with land and people, among other values.…”
Section: Conclusion: the Culture Of Therapymentioning
confidence: 92%
See 3 more Smart Citations
“…The therapy room is a site of intersecting cultural politics -especially the culture of therapy itself. This is founded on the enclosed clinical dyad, which in turn supports the Western ideal of the individual as independent, singular, and separate (Woodard, 2008). Māori clients may however be seeking a much wider collective identity with land and people, among other values.…”
Section: Conclusion: the Culture Of Therapymentioning
confidence: 92%
“…But there are possible pitfalls in this latter process. Woodard's (2008) vignette of Tāwhiri raised the importance of authenticity. If our Māori client is searching for cultural authenticity, how can a Pākehā therapist help if they are culturally unsure, if they are not themselves authentic?…”
Section: Māori Psychotherapy and Historical Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…While Shabad () and Baider et al () did not focus on the impact that intergenerational trauma has on the relationship Māori have with hospice and cancer services, Pihama et al () and Durie () showed that similar phenomena occur in a more generalised perspective amongst Māori through parent–infant attachment. Woodard () added to the korero by exploring the impact the experience of colonisation has had on the identity of Māori. He suggested that it potentially divides and fragments the sense of mana ake (the uniquely ecologically integrated, interconnected sense of self) in Māori, transforming the Māori sense of self into an isolated and objectified “Other”.…”
Section: Cancer As a Māori Health Prioritymentioning
confidence: 99%